Sodar studies of the thermal structure of the lower Troposphere at Delhi - SINGAL, S.P.; AGGARWAL , S. K.; GERA, B. S. (MAUSAM, 1977)
The monostatic sodar system set up at National Physical Laboratory has been operating continuously to study the thermal structure of the lower troposphere upto a vertical height of 350 m. The results obtained from December 1914 through April 1975 a-re presented. The observed structures showing thermal plumes, inversions, instabilities, turbulences etc developing in the atmosphere as a function of space and time have been indexed to indicate the type of meteorological conditions expected for anyone of these indices. To examine if the sodar can be used for 24 hours monitoring of atmospheric refractivity gradients, the intensity of the received echo signal a-t a fixed height of 150 m ha-s been measured using a microphotometer and compared with the refractivity gradient number obtained from radiosonde data. The results show that the two techniques have a good correlation within the limits of the experimental error. These relative values of received intensity have also been used to calculate thermal structure function CT. The computed values of a p have been found to compare well with Panofsky observations, showing, thereby the utility of the sodar echograms to derive information of the atmospheric turbulence parameter.